2010
DOI: 10.1002/jctb.2443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the biomass in the modelling and simulation of the biofiltration of hydrogen sulphide: simulation and experimental validation

Abstract: BACKGROUND: Several models have been developed to simulate the decay of pollutants concentration along the biofilter and to predict its performance. Despite the evidence, it is common that most models ignore the effect of variable biomass along the biofilter. An equation that represents the variable amount of active biomass along the column was included in the modelling of a biotrickling filter; it was obtained by measuring the active biomass at different heights. Validation of the model was carried out using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Results from models that had considered irregular biofilm growth are not better than those that assume a flat layer. However, Silva et al . modeled the variation of active biomass along the biotrickling filter fed with different H 2 S loading rates.…”
Section: Dynamic Modeling Of Sulfide Removal Processesmentioning
confidence: 99%
“…Results from models that had considered irregular biofilm growth are not better than those that assume a flat layer. However, Silva et al . modeled the variation of active biomass along the biotrickling filter fed with different H 2 S loading rates.…”
Section: Dynamic Modeling Of Sulfide Removal Processesmentioning
confidence: 99%
“…It would indicate that there is no limitation for availability of H2S from the gas phase and it also suggest that the biooxidation kinetics limits the biooxidation in the BTF. Silva et al (2010) had shown low Thiele modules for this system. 7 Figure 11 shows a sensitivity analysis of the DMS inhibition constant when the system was fed with 1.2 g·S m -3 h -1 of DMS and 0.1 g·S m -3 h -1 of H2S.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 5 shows the values obtained from T. thioparus inlet cell counts using epifluorescence microscopy. It is possible to observe that there are no important variations in the inlet cell count due to changes in the H2S inlet concentration and only axial biomass profiles are observed by Silva et al (2010).…”
Section: Numeric Solutionmentioning
confidence: 84%
See 1 more Smart Citation
“…(Smith et al, 1996;Deshusses and Cox, 1999;Kennes and Veiga, 2002). Many microbial growth models have been developed to describe biomass accumulation patterns under different operating conditions (Schwarz et al, 2001;Song and Kinney, 2002;Iliuta and Larachi, 2004;Nukunyaa et al, 2005;Silva et al, 2010). Among these models, however, only a few have considered inert biomass, that part of a biomass composed of cells without biological activity.…”
Section: Introductionmentioning
confidence: 99%